Design of Ventilator with Gas Mixing, Tidal Volume, and Humidifier Parameters - Hanifah Fajrin; Edi Susanto; Pamela Sandi Agus Kristianto; Fery Ferizal Herdiyana; Susilo Ari Wibowo (Universitas Muhammadiyah Yogyakarta, 2022)
On the ventilator, there are several important parameters, including gas mixing, which functions to mix oxygen with free air, the tidal volume serves to supply mixed air to the patient, respiratory rate is the frequency of breath given to the patient, and the humidifier functions to regulate the temperature of the air given to the patient. In this research, the author intends to design a ventilator device which uses a working system to open and close the valve to distribute air to the patient. This tool uses several sensors: oxygen sensor KE-25F3, flow sensor yf-s201, pressure sensor MPX 5700, and temperature sensor DS 12B20. The tidal volume (VT) has 3 setting values: 700 ml, 500 ml, and 300 ml. The test is carried out by opening and closing the valve. The respiratory rate has 2 settings of 15 and 20 breaths/minute. In addition, the humidifier has 3 setting modes 32, 35, and 40o C. From the test results, the highest error was obtained in the 300 ml tidal volume test, which was 7.20% and in the respiratory rate test, the highest error value was 0%. The test results with the oxygen concentration parameter obtained the largest error value of 0.1% at 100% oxygen concentration. In testing the temperature and humidity parameters, the largest average error was 2.40% at 40o C setting. So, it can be concluded that the tool is feasible to use because of the level of small error and still within the standard calibration tolerance of 15%.